The konyak nagas an indian frontier tribe / Christoph Von Fürer-Haimendorf - Von Fürer-Haimendorf, Christoph (1969)
Material background, appearnce, dress, and ornament, communitary, tools and housebold implements, landtenure and agriculture, daily life in a Konyak Village; the social structure and its units, morungs as social units; phases of life, pregnancy and birth, premarital affairs of Wakching family, divorce, adultery and illeginimacy, economic obligations between affines; religious beliefs and practices, the fate of the soul, head-hunting rites, the cult of the sky God.